2021
DOI: 10.1186/s12920-020-00837-3
|View full text |Cite
|
Sign up to set email alerts
|

The Genomics of Opioid Addiction Longitudinal Study (GOALS): study design for a prospective evaluation of genetic and non-genetic factors for development of and recovery from opioid use disorder

Abstract: Background The opioid use disorder and overdose crisis in the United States affects public health as well as social and economic welfare. While several genetic and non-genetic risk factors for opioid use disorder have been identified, many of the genetic associations have not been independently replicated, and it is not well understood how these factors interact. This study is designed to evaluate relationships among these factors prospectively to develop future interventions to help prevent or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…GOALS and OPTIN are prospective, observational studies that include the collection of self-reported demographic and perception survey data at enrollment. In addition, participants are asked to grant access to their electronic health records for up to five years prior to baseline enrollment and up to 12 months after baseline enrollment [1].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…GOALS and OPTIN are prospective, observational studies that include the collection of self-reported demographic and perception survey data at enrollment. In addition, participants are asked to grant access to their electronic health records for up to five years prior to baseline enrollment and up to 12 months after baseline enrollment [1].…”
Section: Methodsmentioning
confidence: 99%
“…CORI study enrollment criteria consist of an age of at least 18 years, English language proficiency, written informed consent, willingness to provide a saliva sample for DNA analysis, and either in-treatment status for chronic pain at Cooper University Health Care clinic (OPTIN) or in-treatment status for opioid use disorder at the Center for Healing at Cooper University Health Care as defined by DSM-5 (GOALS) [1].…”
Section: Study Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies are currently underway to understand the genetic factors that may influence treatment-related outcomes among patients receiving MOUD. For example, The Genomics of Opioid Addiction Longitudinal Study (GOALS) will be a prospective observational study of 400 patients receiving MOUD that will help determine the interplay between genetic and non-genetic (e.g., depression, anxiety, adverse childhood experiences) factors on key treatment outcomes (e.g., treatment retention rate, toxicology results, overdoses) 51 . While conducted with typically smaller patient cohorts, neuroimaging studies can provide a vast amount of data per patient.…”
Section: Genomics and Neuroimagingmentioning
confidence: 99%
“…For example, The Genomics of Opioid Addiction Longitudinal Study (GOALS) will be a prospective observational study of 400 patients receiving MOUD that will help determine the interplay between genetic and non-genetic (e.g., depression, anxiety, adverse childhood experiences) factors on key treatment outcomes (e.g., treatment retention rate, toxicology results, overdoses). 51 While conducted with typically smaller patient cohorts, neuroimaging studies can provide a vast amount of data per patient. For example, a recent systematic review of functional magnetic resonance imaging studies found that persons with OUD display heightened neural activation to heroin cues, and this pattern is attenuated by MOUD, predicts treatment response, and is reduced after extended abstinence.…”
Section: Genomics and Neuroimagingmentioning
confidence: 99%